2022
DOI: 10.1242/bio.059491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weighted downhill running training on serial sarcomere number and work loop performance in the rat soleus

Abstract: Increased serial sarcomere number (SSN) has been observed in rats following downhill running training due to the emphasis on active lengthening contractions; however, little is known about the influence on dynamic contractile function. Therefore, we employed 4 weeks of weighted downhill running training in rats, then assessed soleus SSN and work loop performance. We hypothesised trained rats would produce greater net work output during work loops due to a greater SSN. Thirty-one Sprague-Dawley rats were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 93 publications
8
26
0
Order By: Relevance
“…Accordingly, eccentric training has been shown to produce preferential increases in the size of Type II fibers (Douglas et al, 2017 ); however, in the present study, in the training group there was an increased CSA for both Type I and II fibers (Figure 2 ). Recently, Hinks et al ( 2022 ) reported no differences in muscle size or isometric force production for the soleus muscle tested in vitro following 4 weeks of downhill running between the control and training groups. Of note, this is the same sample of rats used for single fiber analysis in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Accordingly, eccentric training has been shown to produce preferential increases in the size of Type II fibers (Douglas et al, 2017 ); however, in the present study, in the training group there was an increased CSA for both Type I and II fibers (Figure 2 ). Recently, Hinks et al ( 2022 ) reported no differences in muscle size or isometric force production for the soleus muscle tested in vitro following 4 weeks of downhill running between the control and training groups. Of note, this is the same sample of rats used for single fiber analysis in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The training protocol consisted of 4 weeks of downhill running training 3 days/week, with custom‐made weighted vests (Hinks et al, 2022 ) to add load during running. Rats ran on an EXER 3/6 animal treadmill (Columbus Instruments) at a 15° decline.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… ABSTRACT First Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Avery Hinks is first author on ‘ Influence of weighted downhill running training on serial sarcomere number and work loop performance in the rat soleus ’, published in BiO. Avery is an MSc student (soon to be PhD student) in the lab of Dr Geoffrey Power at the University of Canada, investigating how muscle structure influences muscle function, particularly regarding adaptations following an intervention.…”
mentioning
confidence: 99%